Prevalence and risk factors of retinopathy of prematurity among preterm neonates admitted to a tertiary care hospital - Rahman, Mohammad M.; Adnan, Mohammad A.; Uddin, Muhammad G.; Haque, Mohammad A.; Ahmed, Mahbub; Islam, Mohammad T. (International Journal of Contemporary Pediatrics, 2026)
Background: Retinopathy of prematurity is a multifactorial vaso-proliferative disorder of the retina affecting mainly premature neonates. We aimed to determine the prevalence of ROP as well as to find out the risk factors behind this. Methods: This cross-sectional analytic study was conducted in the department of neonatology and obstetrics and gynecology of BSMMU, Dhaka, from April 2016 to September 2017. All stable term and stable preterm newborns of both sexes were enrolled. Hemodynamically unstable newborn babies, newborns with congenital anomalies, newborns of<30 weeks, and newborns admitted after 72 hours of age were excluded. 70 samples comprising into two groups, in preterm group 40 and in term group 30 samples were taken. Plasma tocopherol <500 mg/dl was used as a deficient vit-E level. ROP screening was done by an ophthalmologist using a binocular indirect ophthalmoscope. Results: Among 40 pre-term neonates, 12 were diagnosed as ROP with a prevalence of 30%. Stage 1-3 ROP were present among 8, 2 and 2 cases, respectively. There were equal number of males and females (35 each). Deficient vit-E level and SGA were significantly associated with ROP (p=0.05 and p=0.01, respectively). Stepwise multiple logistic regressions of risk factors showed vitamin E deficiency as a significant risk of developing ROP when other risk factors are intercepted. Conclusions: Prevalence of ROP was 30% among pre-term neonates. Deficient vit-E level and SGA were significantly associated with ROP. Vitamin E deficiency resulted significant risk of developing ROP when other risk factors are present.